Ductal obstruction promotes formation of preneoplastic lesions from the pancreatic ductal compartment. Issue 10 (12th December 2018) - Cheng, Tao; Zhang, Zhiheng; Jian, Ziying; Raulefs, Susanne; Schlitter, Anna Melissa; Steiger, Katja; Maeritz, Nadja; Zhao, Yamin; Shen, Shanshan; Zou, Xiaoping; Ceyhan, Güralp O.; Friess, Helmut; et al.
Abstract : Pancreatitis is a significant risk factor for pancreatic ductal adenocarcinoma (PDAC). Previous studies in mice have demonstrated that pancreatitis contributes to oncogenic Kras‐driven carcinogenesis, probably initiated in acinar cells; however, oncogenic Kras alone or in combination with caerulein‐induced pancreatitis is not sufficient in initiating PDAC from the ductal compartment. We thus introduced ductal obstruction – which induces a more severe form of pancreatitis – by pancreatic ductal ligation in mice harbouring oncogenic Kras. This induced a particular phenotype with highly proliferative nonmucinous cells with nuclear atypia. Around these lesions, there was a significant proliferation of activated fibroblasts and infiltration of immune cells, corroborating the pathological features of preneoplastic lesions. Lineage‐tracing experiments revealed that these preneoplastic cells derived from two distinctive cellular sources: acinar and ductal cells. Phenotypic characterisation revealed that the duct‐derived preneoplastic lesions show a high proliferative potential with persistent activation of tumour‐promoting inflammatory pathways while the acinar‐derived ones were less proliferative with persistent p53 activation. Furthermore, the duct‐derived preneoplastic cells have a particularly high nuclear‐to‐cytoplasmic ratio. These data demonstrate that ductal obstruction promotes preneoplastic lesion formation from the pancreatic ductal compartment. Abstract : What's new? Pancreatic inflammation contributes to oncogenic Kras‐driven pancreatic ductal adenocarcinoma (PDAC). Little is known, however, about differences between pancreatic acinar cells and ductal cells regarding susceptibility to oncogenic Kras. Here, initiation of pre‐neoplastic lesions from the acinar or ductal cellular compartment was found to be related to inflammation type and extent. In oncogenic Kras mice, ductal obstruction caused severe pancreatitis with transient ductal cell proliferation and further induced a proliferative phenotype in oncogenic Kras‐expressing ductal cells, with pathological features resembling those of pre‐neoplastic lesions. The findings highlight the significance of cell type‐dependent diversity in PDAC malignant transformation pathways.